CO42 | Oxidative stress may contribute to enhanced thrombopoiesis through miR-150: implications for aspirin response (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Variability in platelet cyclooxygenase-1 (COX-1) turnover affects individual responses to aspirin (ASA). Due to ASA’s short half-life, increased platelet (PLT) production can limit its antiplatelet effect over 24 hours. We previously showed that poor ASA responders have enhanced megakaryopoiesis (MK) and proPLT formation, restoring COX-1 activity more rapidly. Type 2 diabetes mellitus (T2DM) is characterized by elevated oxidative stress, which may alter PLT microRNA (miRNA) profiles, increasing PLT reactivity and resistance to ASA. We evaluated CCL5 (a chemokine promoting MKs) and miR-150 (regulator of MK-erythroid progenitors) in patients with shortened ASA effect (10–24h) and faster PLT COX-1 recovery. We aimed to assess lipid peroxidation (via urinary 8-iso-PGF2α), circulating CCL5, and their association with miR-150.